Development of 3D-printed chocolate fortified with collagen peptides - Jinge Shao; Yujin Cao; Zhipeng Zheng; Shaoling Lin; Yi Zhang; Jiamiao Hu (Journal of Food Engineering, 2027)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Growth-mode-independent glutamine/glutamate/aspartate metabolic shift and urea cycle remodeling driven by FOXA1 in benzo[a]pyrene-transformed human bronchial epithelial cells - Yujin Fu; Yanmin Qi; Yunkun Xing; Yitong Lin; Zhiyu Liu; Juanling Fu; Biyun Yao; Peng Zhao (Toxicology and Applied Pharmacology, 2026)

The interactive effects of climate and land-use changes on soil water erosion across China under shared socioeconomic pathways - Yujin Xia; Wen Dai; Qigen Lin; Yuqi Wang; Wei Shao; Guojie Wang (Journal of Hydrology, 2026)

Integrating DNA tetrahedron with affinity magnetic levitation for selective capture and sensitive detection of circulating tumor cells - Zilong Zhang; Sidi Cun; Yuxuan Yuan; Yujin Lin; Yitao Cao; Yinzi Chen; Jing Zhang; Jing Wang; Xinfeng Zhao (Analytica Chimica Acta, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

NaCl substitution characteristics of Salicornia plant salt and potential application in sturgeon caviar: focus on antibacterial activity and phospholipids oxidation - Weijia Zhang; Lingxin Kong; Jingqi Shen; Yuanhui Zhao; Yujin Li; Shuang Cong; Jian Li; Jinlin Wang; Fan Bai; Peng Xu; Lin Gao; Xinxing Xu (Food Chemistry, 2026)

Customized screening of ACE2 regulatory peptides from oyster to mitigate LPS-induced acute lung injury based on SPR technology - Xiaoyu Xia; Caixing Wen; Wenhong Cao; Xiaoming Qin; Yujin Li; Haisheng Lin; Zhongqin Chen; Huina Zheng; Guoping Zhu; Jialong Gao (Food Bioscience, 2025)

Emission characteristics of biogenic volatile organic compounds in a subtropical pristine forest of southern China - Xi Chen; Daocheng Gong; Youjing Lin; Qiao Xu; Yujin Wang; Shiwei Liu; Qinqin Li; Fangyuan Ma; Jiangyong Li; Shuo Deng; Hao Wang; Boguang Wang (Journal of Environmental Sciences, 2025)

A mixed layer height parameterization in a 3-D chemical transport model: Implications for gas and aerosol simulations - Hyeonmin Kim; Rokjin J. Park; Song-you Hong; Do-Hyeon Park; Sang-Woo Kim; Yujin J. Oak; Xu Feng; Haipeng Lin; Tzung-May Fu (Science of The Total Environment, 2024)

Recycling of manganese ore desulfurization slag for preparation of low-temperature NH3-SCR catalyst with good scale-up production performance - Yuzhu Yang; Runqing Wang; Jie Liu; Yujin Peng; Zhongde Dai; Wenju Jiang; Lu Yao; Lin Yang (Journal of Hazardous Materials, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

New progress of tuberculosis scar carcinoma - Wenwen Sun; Yujin Liu; Lishu Zhao; Hao Wang; Li Ye; Xinyue Liu; Kandi Xu; Yu Chen; Lin Fan (Cancer and Metastasis Reviews, 2023)
It has been demonstrated that scar tissue and fibrosis may increase the likelihood of developing malignancies. Specifically, scar tissue has been linked to the occurrence and progression of lung cancer (LC), though the precise mechanisms necessitate further research for explanation. Lung scarring can stem from various causes, with carcinogenesis on scarring lesions in pulmonary tuberculosis (PTB) being the most frequent (accounting for approximately 75% of cases). Notably, having previously cured, PTB is the second most common risk factor for LC after smoking, with approximately 3% of PTB patients experiencing LC as a secondary condition. This essay will delve into the mechanisms, treatment, and prognosis of tuberculosis scar carcinoma (TSC).

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

A self-assembly hydrophobic oCDs/Ag nanoparticles SERS sensor for ultrasensitive melamine detection in milk - Jiaoyan Qiu; Yujin Chu; Qihang He; Yingkuan Han; Yu Zhang; Lin Han (Food Chemistry, 2023)

Catalytic removal of 2-butanone with ozone over porous spent fluid catalytic cracking catalyst - Yujin Hwang; Young-Min Kim; Jung Eun Lee; Gwang Hoon Rhee; Pau-Loke Show; Kun-Yi Andrew Lin; Young-Kwon Park (Environmental Research, 2023)